Changes in the Key Economic Indicators in Japan, Poland, the United States and the Euro Area in the 21st Century - Ślasko, Karol; Stawska, Joanna (Journal of Finance and Financial Law, 2023)
The aim of the article is to identify the changes of selected economic variables in Japan, Poland, the USA and the euro area and to evaluate the impact of these variables on these economies in 2000–2022. The hypothesis posed in the article: The economies of Japan, Poland, the USA and the euro zone have overcome the economic shocks that occurred in the first two decades of the 21st century. Methodology: The study included a review of the literature on the subject, the presentation and analysis of statistical data, including its graphical presentation. Six economic indicators were selected for analysis, such as: the unemployment rate, inflation, General Government debt, long-term interest rates, GDP per capita, and GDP growth in Japan, Poland, the United States and the euro area in 2000–2022. Results of the research: Over the past 20 years, economies have been hit by unprecedented crises such as the Global Financial Crisis (GFC) and Covid-19, and yet we note that the surveyed countries and the euro zone showed positive economic growth for most of the period and successfully fought unemployment. Japan tried to get out of periods of deflation, but out of the examined 23 years, deflation was recorded in Japan for 15 years. In the years 2000–2022, the highest economic growth was most often recorded in Poland and the lowest in Japan, but the highest inflation was also most often recorded in Poland. In all the surveyed countries and the euro zone, a tendency to increase the GG of debt was clearly noticed.